C1q as a target molecule to treat human disease: What do mouse studies teach us? - Schulz, Kristina; Trendelenburg, Marten (Frontiers in Immunology, 2022)
The complement system is a field of growing interest for pharmacological intervention. Complement protein C1q, the pattern recognition molecule at the start of the classical pathway of the complement cascade, is a versatile molecule with additional non-canonical actions affecting numerous cellular processes. Based on observations made in patients with hereditary C1q deficiency, C1q is protective against systemic autoimmunity and bacterial infections. Accordingly, C1q deficient mice reproduce this phenotype with susceptibility to autoimmunity and infections. At the same time, beneficial effects of C1q deficiency on disease entities such as neurodegenerative diseases have also been described in murine disease models. This comprehensive review provides an overview of all currently available literature on the C1q knockout mouse in disease models to identify potential target diseases for treatment strategies focusing on C1q, and discusses potential side-effects when depleting and/or inhibiting C1q